Respuesta :

Answer:

Simplifying

6 + -8x = 7x + -9x + -36

Reorder the terms:

6 + -8x = -36 + 7x + -9x

Combine like terms: 7x + -9x = -2x

6 + -8x = -36 + -2x

Solving

6 + -8x = -36 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.

6 + -8x + 2x = -36 + -2x + 2x

Combine like terms: -8x + 2x = -6x

6 + -6x = -36 + -2x + 2x

Combine like terms: -2x + 2x = 0

6 + -6x = -36 + 0

6 + -6x = -36

Add '-6' to each side of the equation.

6 + -6 + -6x = -36 + -6

Combine like terms: 6 + -6 = 0

0 + -6x = -36 + -6

-6x = -36 + -6

Combine like terms: -36 + -6 = -42

-6x = -42

Divide each side by '-6'.

x = 7

Simplifying

x = 7

Answer:

x = 7

Hope This Helps! :) Please Give brainliest if you can!

Ver imagen abiafalak8

Otras preguntas